Importance of the Strategic Tourist Model Pentur 2016-2025 as Based on a Local Development Context - Begazo Villanueva, José Domingo (2017)
This article aims to present reflections on the importance and relevance of tourism development in local development processes.In Peru, its application and implementation is a major challenge to optimize the Local Economic Development of Regions specifically rural areas of our country.In the final reflections stresses that local economic development is a process that promotes the acceleration and growth of our communities in a given territorial circle, it is also noted that these processes include tissues such as decisiveness, management and stakeholder participation local.With the alter emphasis, tourism can be promoted as an economic activity, innovation and dynamism that contribute to the processes of Local Development of a Territory, however that can be managed in an appropriate manner requires a key tool: The Model Tourism.